2005
DOI: 10.1088/0967-3334/27/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 50 Hz magnetic field exposure on human heart rate variability with passive tilting

Abstract: The question of whether power-frequency magnetic fields of strengths relevant to industrial exposure can affect heart rhythm remains controversial. Because the reported effects on heart rate (HR) are so small, procedures which can provoke changes in the sympathovagal balance in a controlled manner may have a greater capacity for identifying subtle field-related changes, if they do exist. We have investigated HR and heart rate variability (HRV) spectral indices in 20 volunteers subjected to a tilt from the supi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
5
18
0
Order By: Relevance
“…. Other investigators have experienced similar difficulty demonstrating a reproducible MF effect on HR and HRV (Sait et al 2006;Ghione et al 2005;Kurokawa et al 2003). The results of the present study support the findings of these researchers who have reported an absence of MF effects.…”
Section: Skin Blood Perfusionsupporting
confidence: 91%
“…. Other investigators have experienced similar difficulty demonstrating a reproducible MF effect on HR and HRV (Sait et al 2006;Ghione et al 2005;Kurokawa et al 2003). The results of the present study support the findings of these researchers who have reported an absence of MF effects.…”
Section: Skin Blood Perfusionsupporting
confidence: 91%
“…These results were in agreement with their earlier results demonstrating that a 37 Hz, 80 T exposure did not result in alterations of cardiac rhythm (Ghione et al 2004). In a shift of research focus, Sait et al (2006) designed a study that provoked controlled changes in the sympathetic-parasympathetic balance in order to determine if there were any subtle Weld related changes. Using a 50 Hz, 28 T Xux density exposure chamber, they subjected 20 volunteers to a 15 min, 60° body tilt experimental session.…”
Section: Laboratory Studiessupporting
confidence: 90%
“…The paced respiration helped avoid any interference of the low frequency HRV spectrum from slow breaths while tilted. No eVect of the Weld was reported for either HR or HRV, contesting the suggestion by Sastre et al that sympathetic neural stimulation is required for Weld induced changes in ANS control (Sait et al 2006). The question of whether the paced respiration might have masked any Weld related HRV changes arises though, as it was reported that several subjects had diYculty maintaining the prescribed rate.…”
Section: Laboratory Studiesmentioning
confidence: 59%
“…HR was measured by detecting the intervals between the two QRS (electrical wave of cardiac ventricular muscle contraction). Sait et al (2006) found that HR slowed down with exposure to magnetic field. They indicated that continuous exposure to a magnetic field affected both HR and HRV and, as the strength of the field increased, the effect became significant.…”
Section: Introductionmentioning
confidence: 99%